Single-walled carbon nanotube conductive paste and preparation method and application thereof

By modifying single-wall carbon nanotubes and optimizing graphene, the problem of poor agglomeration and dispersion of single-wall carbon nanotubes is solved, and a stable dispersion conductive paste is formed, which significantly improves the circulation performance of lithium-ion batteries. .

CN119418985APending Publication Date: 2025-02-11CONE SCI CITY GUANGZHOU ADVANCED MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411297039.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Single-wall carbon nanotubes are very prone to agglomeration due to their large specific surface area, and their dispersion and stability in various solvents are very low, making it difficult to form a stable dispersed conductive paste, which affects its performance as a conductive agent, and thus leads to lithium. The cycling performance of ion batteries cannot be effectively improved.

Method used

Use coupling agent to modify single-wall carbon nanotubes and optimize graphene specifications to make graphene easier to enter the modified single-wall carbon nanotube tube tubes to block, separate the single-wall carbon nanotube tube tube bundles, and improve the Dispersive performance. At the same time, a dispersion process of multiple high-pressure dispersion and grinding is adopted to form a relatively stable dispersed single-wall carbon nanotube conductive paste.

Benefits of technology

The dispersion and stability of single-wall carbon nanotubes are significantly improved, and a stable dispersion conductive paste is formed, which improves the conductive performance and improves the circulation performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119418985A_ABST
    Figure CN119418985A_ABST
Patent Text Reader

Abstract

The invention discloses a single-walled carbon nanotube conductive paste and a preparation method and application thereof, and relates to the technical field of materials. The single-walled carbon nanotube conductive paste provided by the invention comprises the following components in percentage by weight: 0.2%-2% of modified single-walled carbon nanotubes, 0.2%-2% of a coupling agent, 0.1%-2% of a coupling agent and the balance of a solvent, wherein the modified single-walled carbon nanotube comprises a coupling agent modified single-walled carbon nanotube; 0.1%-1% of graphene; wherein the graphene at least comprises single-layer graphene; 0.5%-2% of a total surfactant; 0.5%-2% of a total dispersant; and the total solvent accounts for 93%-98.7%. The single-walled carbon nanotubes are not easy to agglomerate, and have good dispersibility and stability in the single-walled carbon nanotube conductive paste, so that the stably dispersed single-walled carbon nanotube conductive paste is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material technology, and specifically relates to a single-walled carbon nanotube conductive slurry and a preparation method and application thereof. Background Art

[0002] Single-walled carbon nanotubes (SWCNTs) are composed entirely of carbon atoms, and their geometric structure can be considered to be equivalent to the structure of a circular ring of rolled graphene, or it can also be considered to be equivalent to the structure of a graphene plane mapped onto a cylinder, while the hexagon of graphene remains unchanged during the mapping process. Therefore, SWCNTs have a high specific surface area (its specific surface area is comparable to that of graphene, up to about 2630 m 2 / g), large aspect ratio, good flexibility, good crystal structure, good electrical conductivity and good thermal conductivity, and is widely used as a conductive agent for negative electrode sheets in lithium-ion batteries.

[0003] The negative electrode of lithium-ion batteries can be made of silicon-based negative electrode materials. Silicon-based negative electrode materials often have volume expansion and particle pulverization (becoming silicon-based negative electrode particles) problems during the lithium insertion process, making it impossible for them to contact the conductive agent completely, causing the active material that is not in contact with the conductive agent to become inactivated material, thereby causing the cycle performance of lithium-ion batteries to be greatly attenuated. Single-walled carbon nanotubes are used in silicon-based negative electrode materials and can be wrapped around the surface of silicon-based negative electrode particles, which is conducive to improving the volume expansion and particle pulverization problems of silicon-based negative electrode materials, thereby improving the cycle performance of lithium-ion batteries.

[0004] However, the specific surface area of ​​SWCNT is too large, which makes it very easy to agglomerate. Its dispersibility and stability in various solvents are very low, making it difficult to form a stably dispersed conductive slurry, which affects its performance as a conductive agent and thus leads to the inability to effectively improve the cycle performance of lithium-ion batteries. Summary of the invention

[0005] The purpose of the present application is to overcome the above-mentioned deficiencies of the prior art and to provide a single-walled carbon nanotube conductive slurry and a preparation method and application thereof, so as to solve the problem that the existing single-walled carbon nanotubes have too large specific surface area, are very easy to agglomerate, have low dispersibility and stability in various solvents, and are difficult to form a stably dispersed conductive slurry.

[0006] In order to achieve the above application purpose, the first aspect of the present application provides a single-walled carbon nanotube conductive paste. Taking the total weight of the single-walled carbon nanotube conductive paste as 100%, the single-walled carbon nanotube conductive paste comprises:

[0007] Modified single-walled carbon nanotubes, 0.2%-2%; wherein the modified single-walled carbon nanotubes include single-walled carbon nanotubes modified by coupling agents;

[0008] Graphene, 0.1%-1%; wherein the graphene comprises at least a single layer of graphene;

[0009] Total surfactant, 0.5%-2%;

[0010] Total dispersant, 0.5%-2%;

[0011] Total solvents, 93%-98.7%.

[0012] Furthermore, the single-walled carbon nanotube conductive paste further comprises, by weight:

[0013] Binder, 0.5%-3%.

[0014] Furthermore, the weight ratio of the modified single-walled carbon nanotube to the graphene is in the range of 3:1-5:1.

[0015] Furthermore, the average outer diameter of the modified single-walled carbon nanotubes is less than 5 nm;

[0016] The average outer diameter of the modified single-walled carbon nanotubes is set to X, the standard deviation of the outer diameter of the modified single-walled carbon nanotubes is set to Y, 3nm≤X±2Y≤7nm; wherein 0<Y≤1.

[0017] Furthermore, the graphene is a single-layer graphene, and a size of the single-layer graphene in a length direction is greater than 1000 nm, and a size in a width direction is less than or equal to 100 nm.

[0018] Further, the graphene is composed of a single-layer graphene and a double-layer graphene, the size of the single-layer graphene in the length direction is greater than 1000nm, and the size in the width direction is less than or equal to 100nm, and the size of the double-layer graphene in the length direction is greater than 1000nm, and the size in the width direction is less than or equal to 100nm;

[0019] and / or,

[0020] The percentage content of the single-layer graphene in the graphene is greater than or equal to 80%.

[0021] In a second aspect of the present application, a lithium-ion battery is provided, comprising a negative electrode plate, wherein the negative electrode plate comprises the above-mentioned single-walled carbon nanotube conductive slurry.

[0022] The third aspect of the present application provides a method for preparing the above-mentioned single-walled carbon nanotube conductive paste, comprising the following steps:

[0023] Step 1, forming a graphene dispersion and the modified single-walled carbon nanotubes respectively;

[0024] Step 2: dispersing the modified single-walled carbon nanotubes into the second part of the solvent, adding the graphene dispersion, the third part of the surfactant and the fourth part of the dispersant, performing a dispersion treatment at a first pressure, and then performing a grinding treatment at a first speed to obtain a mixture; wherein the second part of the solvent is a part of the total solvent;

[0025] Step three, adding the fifth part of the surfactant and the sixth part of the dispersant to the mixture, and then repeating the steps of dispersing under the first pressure and grinding at the first speed in step two to obtain the single-walled carbon nanotube conductive slurry; wherein the fifth part of the surfactant is the remaining surfactant in the total surfactant except the third part of the surfactant, and the sixth part of the dispersant is the remaining dispersant in the total dispersant except the fourth part of the dispersant.

[0026] Further, forming the modified single-walled carbon nanotubes comprises:

[0027] The single-walled carbon nanotubes are dispersed in a coupling agent solution for dispersion treatment, and then filtered and dried to obtain the modified single-walled carbon nanotubes.

[0028] Further, forming the graphene dispersion comprises:

[0029] The graphene is dispersed in the first part of the solvent for dispersion treatment to obtain the graphene dispersion liquid; wherein the first part of the solvent is the solvent in the total solvent except the second part of the solvent.

[0030] Compared with the prior art, this application has the following technical effects:

[0031] The single-walled carbon nanotube conductive slurry and its preparation method and application provided in the embodiments of the present application respectively use coupling agents to modify the single-walled carbon nanotubes and optimize graphene, so that graphene can more easily enter the tube bundles of the modified single-walled carbon nanotubes for barrier, better separate the tube bundles of the single-walled carbon nanotubes, make the single-walled carbon nanotubes less likely to agglomerate, improve the dispersion performance of the single-walled carbon nanotubes, and greatly improve the dispersion and stability of the single-walled carbon nanotubes. In addition, the dispersion process is optimized, and a combination of multiple high-pressure dispersions and grinding is used to achieve good dispersion of the single-walled carbon nanotubes while reducing damage to the single-walled carbon nanotube structure, thereby forming a relatively stably dispersed single-walled carbon nanotube conductive slurry, which is simple and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0033] Figure 1 is a flow chart of a process for preparing a graphene dispersion provided in an embodiment of the present application;

[0034] Figure 2 This is a process flow chart of a modified single-walled carbon nanotube preparation method provided in an embodiment of the present application;

[0035] Figure 3 is another process flow chart of preparing modified single-walled carbon nanotubes provided in an embodiment of the present application;

[0036] Figure 4 This is a process flow chart for preparing a single-walled carbon nanotube conductive paste provided in an embodiment of the present application. DETAILED DESCRIPTION

[0037] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0038] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0039] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or multiple, respectively.

[0040] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0041] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0042] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be a well-known mass unit such as μg, mg, g, kg, etc.

[0043] The terms "first", "second", etc. are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features.

[0044] In a first aspect, an embodiment of the present application provides a single-walled carbon nanotube conductive paste. Taking the total weight of the single-walled carbon nanotube conductive paste as 100%, the single-walled carbon nanotube conductive paste includes the following components: modified single-walled carbon nanotubes, 0.2%-2%, wherein the modified single-walled carbon nanotubes include single-walled carbon nanotubes modified by coupling agents; graphene, 0.1%-1%, wherein the graphene includes at least single-layer graphene; total surfactants, 0.5%-2%; total dispersants, 0.5%-2%; total solvents, 93%-98.7%.

[0045] Taking the total weight of the single-walled carbon nanotube conductive paste as 100%, the modified single-walled carbon nanotubes can be 0.2%, 0.7%, 1%, 1.3%, 1.6% or 2%, etc., the graphene can be 0.1%, 0.2%, 0.4%, 0.6%, 0.8% or 1%, etc., the total surfactant can be 0.5%, 0.8%, 1%, 1.4%, 1.7% or 2%, etc., the total dispersant can be 0.5%, 0.8%, 1%, 1.5%, 1.7% or 2%, etc., the total solvent can be 93%, 94.2%, 95.9%, 96%, 97.5% or 98.7%, etc.

[0046] In the application, the average outer diameter of the modified single-walled carbon nanotubes can be less than 5nm. At the same time, when the average outer diameter of the modified single-walled carbon nanotubes is set to X and the standard deviation of the outer diameter of the modified single-walled carbon nanotubes is set to Y, X±2Y satisfies: 3nm≤X±2Y≤7nm, wherein 0<Y≤1. For example, the average outer diameter of the modified single-walled carbon nanotubes can be 3.2nm, 3.5nm, 4nm, 4.2nm, 4.5nm or 4.8nm. Thus, the diameter of the modified single-walled carbon nanotubes is smaller, the diameter distribution is narrower, the purity of the single-walled carbon nanotubes is higher, and they can be well dispersed in the single-walled carbon nanotube conductive paste, and it is easier to form a conductive path, thereby improving the conductive performance of the single-walled carbon nanotube conductive paste; in addition, when the single-walled carbon nanotubes with a high aspect ratio are applied to silicon-based negative electrode materials, it is easier to bind the silicon-based negative electrode materials, which is beneficial to improve the volume expansion and particle pulverization problems of the silicon-based negative electrode materials, thereby improving the cycle performance of lithium-ion batteries.

[0047] It should be noted that the coupling agent mainly plays a role in surface modification of single-walled carbon nanotubes. Specifically, the organic groups in the coupling agent can interact with the surface of the single-walled carbon nanotubes to form an organic film, which can increase the hydrophobicity or hydrophilicity of the surface of the single-walled carbon nanotubes and change the surface properties of the single-walled carbon nanotubes.

[0048] In applications, graphene sheets can be inserted into disordered single-walled carbon nanotubes, effectively separating the distance between single-walled carbon nanotube bundles and preventing the formation of tightly entangled clusters. Therefore, graphene is used to improve the dispersion performance of single-walled carbon nanotubes.

[0049] The graphene is a single-layer graphene. Except for the thickness direction, the size of the single-layer graphene in the length direction is greater than 1000nm, and the size in the width direction is less than or equal to 100nm. For example, the average value of the size of the single-layer graphene in the length direction can be 1300nm, 1500nm, 1800nm, 2000nm, 2200nm or 2400nm, etc., and the average value of the size of the single-layer graphene in the width direction can be 41nm, 43nm, 45nm, 48nm, 50nm, 52nm or 56nm, etc. Therefore, the graphene composed of the single-layer graphene with this size belongs to the thin long sheet graphene, which is easier to insert between the bundles of the modified single-walled carbon nanotubes, so that the modified single-walled carbon nanotubes can be better dispersed.

[0050] Graphene is composed of a single-layer graphene and a double-layer graphene. The size of the single-layer graphene in its length direction is greater than 1000nm, and the size in its width direction is less than or equal to 100nm, except for its thickness direction. For example, the average value of the size of the single-layer graphene in its length direction may be 1300nm, 1500nm, 1800nm, 2000nm, 2200nm or 2400nm, and the average value of the size of the single-layer graphene in its width direction may be 41nm, 43nm, 45nm, 48nm, 500nm, 510nm, 520nm, 530nm, 540nm, 550nm, 560nm, 570nm, 580nm, 590nm, 610nm, 620nm, 630nm, 640nm, 650nm, 660nm, 670nm, 680nm, 690nm, 700nm, 710nm, 720nm, 730nm, 740nm, 750nm, 760nm, 770nm, 780nm, 790nm, 800nm, 810nm, 820nm, 830nm, 840nm, 850nm, 860nm, 870nm, 880nm, 890nm, 900nm, 910nm, 920nm, 930nm, 940nm, 950nm, 960nm, 970nm, 980nm, 990nm, 1000nm The size of the double-layer graphene in the length direction is greater than 1000nm, and the size in the width direction is less than or equal to 100nm, except for the thickness direction. For example, the average value of the size of the double-layer graphene in the length direction can be 1500nm, 1800nm, 2000nm, 2200nm, 2400nm or 2600nm, and the average value of the size of the double-layer graphene in the width direction can be 42nm, 44nm, 46nm, 50nm, 52nm or 56nm. Thus, the graphene composed of the single-layer graphene and the double-layer graphene with the above-mentioned size belongs to the graphene in the form of thin long sheets, which is easier to be inserted between the bundles of the modified single-walled carbon nanotubes, so that the modified single-walled carbon nanotubes can be better dispersed.

[0051] In the case where graphene is obtained by processing single-layer graphene and double-layer graphene, the percentage content of single-layer graphene in graphene (also referred to as single-layer rate) can be greater than or equal to 80%, and illustratively, the single-layer rate can be 80%, 84%, 88%, 90%, 95% or 99%, etc. Since single-layer graphene is thinner, it is easier to enter the bundle of modified single-walled carbon nanotubes for separation to prevent agglomeration. Therefore, the content of single-layer graphene is set higher, so that the bundle of single-walled carbon nanotubes can be better separated, so that it is not easy to agglomerate into a group, and the dispersion performance of single-walled carbon nanotubes is improved.

[0052] On the basis of the above, the weight ratio of the modified single-walled carbon nanotube to the graphene can be in the range of 3:1-5:1. For example, the weight ratio of the modified single-walled carbon nanotube to the graphene can be 3:1, 3.5:1, 4:1, 4.5:1, 4.8:1 or 5:1, etc. Thus, the graphene has a better effect of separating the distance between the single-walled carbon nanotube bundles, further improving the overall dispersion performance of the single-walled carbon nanotubes.

[0053] In applications, the surfactant may include one or more combinations of hexadecyl trimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS), sodium dodecyl benzene sulfonate (SDBS), polyvinyl pyrrolidone (PVP), etc.

[0054] In applications, the dispersant may include one or more combinations of PVP and its modified copolymers, polyvinylidene chloride (PVDC) and its modified copolymers, cellulose ether derivatives, polyvinyl alcohol and its modified copolymers, and the like.

[0055] The cellulose ether derivatives herein may include lithium carboxymethyl cellulose, hydroxypropyl cellulose, ethyl cellulose and the like.

[0056] As an example, when the dispersant includes lithium carboxymethyl cellulose and PVP, the mass ratio of lithium carboxymethyl cellulose to PVP may be 1:3.

[0057] As another example, when the dispersant includes hydroxypropyl cellulose and PVP, the mass ratio of hydroxypropyl cellulose to PVP may be 1:2.

[0058] As yet another example, when the dispersant includes polyvinyl alcohol and PVP, the mass ratio of polyvinyl alcohol to PVP may be 1:4.

[0059] In applications, the solvent may include one or more combinations of N-methylpyrrolidone, triethyl phosphate, ethanol, isopropanol, water, and the like.

[0060] The embodiment of the present application provides a single-walled carbon nanotube conductive paste, which uses a coupling agent to modify the single-walled carbon nanotubes. Graphene can more easily enter between the bundles of the modified single-walled carbon nanotubes to provide barriers, thereby effectively separating the bundles of the single-walled carbon nanotubes. At the same time, the optimized graphene can better separate the bundles of the single-walled carbon nanotubes, making it difficult for the single-walled carbon nanotubes to agglomerate, thereby greatly improving the dispersion performance of the single-walled carbon nanotubes in the conductive paste, and greatly improving the dispersion and stability of the single-walled carbon nanotubes, thereby forming a stably dispersed conductive paste.

[0061] Furthermore, the single-walled carbon nanotube conductive paste provided in the embodiment of the present application may further include the following components based on the total weight of the single-walled carbon nanotube conductive paste being 100%: a binder, 0.5%-3%.

[0062] For example, based on 100% of the total weight of the single-walled carbon nanotube conductive paste, the binder may be 0.5%, 1%, 1.5%, 2%, 2.5% or 3%, etc.

[0063] In applications, the binder may be a substance with viscosity, for example, at least one of styrene-butadiene rubber and polyacrylic acid.

[0064] The embodiment of the present application provides a single-walled carbon nanotube conductive paste. By adding a binder, the overall viscosity of the single-walled carbon nanotube conductive paste can be increased, and the dispersion effect of the single-walled carbon nanotubes can be stabilized, making it less likely to stratify and settle, etc., thereby further improving the performance of the single-walled carbon nanotube conductive paste.

[0065] In the second aspect, based on the formula of the single-walled carbon nanotube conductive paste, the preparation method of the single-walled carbon nanotube conductive paste is described.

[0066] First, if Figure 1 As shown, the present application embodiment provides a method for preparing a graphene dispersion, comprising the following steps:

[0067] S01. dispersing graphene in the first part of the solvent for dispersion treatment to obtain a graphene dispersion liquid.

[0068] The first part of the solvent is the solvent other than the second part of the solvent in the total solvent, that is, the first part of the solvent is the solvent that accounts for a part of the total solvent in the single-walled carbon nanotube conductive paste formula. The percentage of the first part of the solvent to the total solvent is not specifically limited here. For example, the percentage of the first part of the solvent to the total solvent can be 30%, 35%, 40%, 50% or 60%, etc.

[0069] The above-mentioned dispersion treatment may specifically be: high-speed stirring is performed at a rotation speed of 800 rpm-1200 rpm to achieve the dispersion treatment.

[0070] The viscosity of the prepared graphene dispersion may range from 1500 Pa·s to 2000 mPa·s. For example, the viscosity of the graphene dispersion may be 1500 Pa·s, 1600 Pa·s, 1700 Pa·s, 1800 Pa·s, 1900 Pa·s or 2000 Pa·s, etc. The graphene dispersion having such a viscosity may well disperse the single-walled carbon nanotubes.

[0071] Then, if Figure 2 As shown, the present invention provides a method for preparing modified single-walled carbon nanotubes, comprising the following steps:

[0072] S02. Dispersing the single-walled carbon nanotubes in a coupling agent solution for dispersion treatment, and then sequentially performing suction filtration treatment and drying treatment to obtain modified single-walled carbon nanotubes.

[0073] Based on the total weight of the single-walled carbon nanotube conductive paste as 100%, the coupling agent can be 0.1%-1%. For example, the coupling agent can be 0.1%, 0.2%, 0.4%, 0.6%, 0.8% or 1%.

[0074] The mass percentage of the coupling agent in the coupling agent solution may be in the range of 3wt%-5wt%. For example, the mass percentage of the coupling agent in the coupling agent solution may be 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%.

[0075] The coupling agent may include a silane coupling agent. Specifically, the silane coupling agent may include a silane coupling agent containing one of the functional groups such as isocyanate, amino, carboxyl, epoxy, and mercapto, for example, γ-glycidyloxypropyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane (A-187), γ-aminopropyltriethoxysilane (KH-550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), etc.

[0076] The mass ratio of the single-walled carbon nanotube to the silane coupling agent may be in the range of 1:1-1:1.5. For example, the mass ratio of the single-walled carbon nanotube to the silane coupling agent may be 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5.

[0077] Therefore, by modifying the single-walled carbon nanotubes with a silane coupling agent, the dispersion performance of the modified single-walled carbon nanotubes can be improved.

[0078] Furthermore, if Figure 3 As shown, the above step S02. dispersing the single-walled carbon nanotubes in a coupling agent solution, performing dispersion treatment, and then successively performing suction filtration and drying to obtain the modified single-walled carbon nanotubes may include:

[0079] S021. Disperse the single-walled carbon nanotubes in the silane coupling agent solution, stir evenly first, and then disperse evenly under the action of ultrasound. After the reaction is completed, filter it through a suction filtration mechanism. The surface of the filter membrane is the dispersed single-walled carbon nanotubes. After drying, modified single-walled carbon nanotubes (i.e., single-walled carbon nanotubes that have been surface treated with a silane coupling agent) are obtained.

[0080] In practical applications, the above-mentioned filtration mechanism can be a filtration machine, for example, a vacuum filtration machine, etc.

[0081] Then, if Figure 4 As shown, the embodiment of the present application provides a method for preparing a single-walled carbon nanotube conductive paste, comprising the following steps:

[0082] S1. Dispersing the modified single-walled carbon nanotubes into the second part of the solvent, adding the graphene dispersion, the third part of the surfactant and the fourth part of the dispersant, performing a dispersion treatment at a first pressure, and then performing a grinding treatment at a first rotation speed to obtain a mixture.

[0083] Among them, the second part of the solvent is the remaining solvent in the total solvent of the single-walled carbon nanotube conductive paste except the first part of the solvent, that is, the remaining solvent after deducting the first part of the solvent from the total solvent in the single-walled carbon nanotube conductive paste formula. The percentage of the second part of the solvent in the total solvent in the single-walled carbon nanotube conductive paste formula needs to be determined based on the percentage of the first part of the solvent in the total solvent in the single-walled carbon nanotube conductive paste formula. Exemplarily, when the first part of the solvent is 30%, the second part of the solvent is 70%; or, when the first part of the solvent is 40%, the second part of the solvent is 60%.

[0084] The third part of the surfactant is a surfactant that accounts for a portion of the total amount of surfactants in the single-walled carbon nanotube conductive paste formula. There is no specific limitation on the percentage of the third part of the surfactant in the total amount of surfactants in the single-walled carbon nanotube conductive paste formula. For example, the percentage of the third part of the surfactant in the total amount of surfactants in the single-walled carbon nanotube conductive paste formula can be 30%, 35%, 40%, 50% or 60%, etc.

[0085] The fourth part of the dispersant is a dispersant that accounts for a portion of the total dispersant dosage in the single-walled carbon nanotube conductive paste formula. There is no specific limitation on the percentage of the fourth part of the dispersant in the total dispersant dosage in the single-walled carbon nanotube conductive paste formula. For example, the percentage of the fourth part of the dispersant in the total dispersant dosage in the single-walled carbon nanotube conductive paste formula can be 30%, 35%, 40%, 50% or 60%, etc.

[0086] In applications, the above dispersion and grinding treatments can be performed multiple times, so that the single-walled carbon nanotubes can be dispersed more evenly. Preferably, the dispersion and grinding treatments can be performed at least four times.

[0087] It should be noted that in the above steps, no chemical reaction occurs between graphene and the single-arm carbon nanotube.

[0088] S2. Add the fifth part of the surfactant and the sixth part of the dispersant, and repeat the steps S1 to sequentially disperse at the first pressure and grind at the first speed to obtain a single-walled carbon nanotube conductive slurry with a viscosity ranging from 3000cP to 6000cP.

[0089] It should be noted that the fifth part of the surfactant is the remaining part of the surfactant except for the third part of the surfactant, that is, the remaining surfactant after deducting the third part of the surfactant from the total amount of surfactant in the single-walled carbon nanotube conductive paste formula. The percentage of the fifth part of the surfactant in the total amount of surfactant in the single-walled carbon nanotube conductive paste formula needs to be determined based on the percentage of the third part of the surfactant in the total amount of surfactant in the single-walled carbon nanotube conductive paste formula. Exemplarily, when the third part of the surfactant is 30%, the fifth part of the surfactant is 70%; or, when the third part of the surfactant is 40%, the fifth part of the surfactant is 60%.

[0090] The sixth part of the dispersant is the remaining part of the dispersant except the fourth part of the dispersant dosage, that is, the remaining dispersant after deducting the fourth part of the dispersant dosage from the total dispersant dosage in the single-walled carbon nanotube conductive paste formula. The percentage of the sixth part of the dispersant dosage in the total dispersant dosage in the single-walled carbon nanotube conductive paste formula needs to be determined based on the percentage of the fourth part of the dispersant dosage in the total dispersant dosage in the single-walled carbon nanotube conductive paste formula. Exemplarily, when the fourth part of the dispersant dosage is 30%, the sixth part of the dispersant dosage is 70%; or, when the fourth part of the dispersant dosage is 40%, the sixth part of the dispersant dosage is 60%.

[0091] Furthermore, the above-mentioned step S1. dispersing the modified single-walled carbon nanotubes into the second part of the solvent, then adding the graphene dispersion, the third part of the surfactant and the fourth part of the dispersant, dispersing under a first pressure, and then grinding at a first speed to obtain a mixture can be specifically: re-ultrasonic dispersing the modified single-walled carbon nanotubes into the remaining solvent minus the amount of the first part of the solvent, then adding the graphene dispersion, the third part of the surfactant and the fourth part of the dispersant, high-pressure dispersion at a dispersion pressure of 1000bar-1200bar, and then grinding at a speed of 500rpm-700rpm, at least 4 times, to obtain a mixture.

[0092] It should be noted that the modified single-walled carbon nanoparticles, graphene, coupling agents, surfactants, dispersants and solvents in the embodiments of the present application can all refer to the above embodiments and will not be described in detail here.

[0093] The preparation method of the single-walled carbon nanotube conductive paste provided in the embodiment of the present application, on the one hand, by using a coupling agent to modify the single-walled carbon nanotubes and optimizing the graphene specifications, it is possible for the graphene to more easily enter the tube bundles of the single-walled carbon nanotubes modified by the coupling agent for barrier, and can better separate the tube bundles of the single-walled carbon nanotubes, making it difficult for the single-walled carbon nanotubes to agglomerate, thereby greatly improving the dispersion performance of the single-walled carbon nanotubes, and greatly improving the dispersion and stability of the single-walled carbon nanotubes; on the other hand, the dispersion process is optimized, and a dispersion method combining multiple high-pressure dispersions and grinding is adopted, which can achieve good dispersion of the single-walled carbon nanotubes while reducing damage to the structure of the single-walled carbon nanotubes, and form a relatively stable and dispersed conductive paste in a simple and easy manner.

[0094] The following uses a number of specific embodiments to illustrate the preparation method and application of the single-walled carbon nanotube conductive paste provided in the embodiments and comparative examples of the present application.

[0095] 1. Embodiments of the single-walled carbon nanotube conductive paste and its preparation method of the present application:

[0096] Example 1

[0097] 1. Single-walled carbon nanotube conductive paste formula:

[0098] Taking the total weight of the single-walled carbon nanotube conductive paste as 100%, the single-walled carbon nanotube conductive paste includes KH-550 modified single-walled carbon nanotubes: 0.2%, graphene: 0.1%, total SDS: 0.5%, total carboxymethyl cellulose lithium + PVP (the mass ratio of carboxymethyl cellulose lithium to PVP is 1:3): 0.5%, and total water: 98.7%.

[0099] Among them, the weight ratio of KH-550 modified single-walled carbon nanotubes to graphene is 3:1.

[0100] The average outer diameter of the single-walled carbon nanotubes modified by KH-550 is 3.5 nm, and 3 nm ≤ X ± 2 Y ≤ 7 nm.

[0101] The graphene is made of single-layer graphene and double-layer graphene. The average value of the size of the single-layer graphene in its length direction is 1300nm, the average value of the size of the single-layer graphene in its width direction is 41nm, the average value of the size of the double-layer graphene in its length direction is 1500nm, the average value of the size of the double-layer graphene in its width direction is 42nm, and the monolayer rate is 80%.

[0102] 2. Preparation of graphene dispersion:

[0103] The single-layer graphene and the double-layer graphene are dispersed in the first part of water (the first part of water accounts for 30% of the total water in the single-walled carbon nanotube conductive slurry formula), and stirred at a high speed of 1000 rpm. After dispersion treatment, a graphene dispersion with a viscosity of 1500 mPa·s is obtained.

[0104] 3. Preparation of single-walled carbon nanotubes:

[0105] The single-walled carbon nanotubes are dispersed in a KH-550 solution (the mass percentage of KH-550 in the solution is 5wt%), first stirred evenly, and then evenly dispersed under ultrasonic action. After the reaction is completed, suction filtration is performed through a suction filtration mechanism, and the surface of the filter membrane is the dispersed single-walled carbon nanotubes. After drying, the surface-treated single-walled carbon nanotubes are obtained.

[0106] The mass ratio of single-walled carbon nanotubes to KH-550 is 1:1.

[0107] 4. Preparation of Single-walled Carbon Nanotube Conductive Slurry

[0108] (1). The single-walled carbon nanotubes surface-treated with KH-550 were re-ultrasonic dispersed in the remaining water (the remaining water accounted for 70% of the total water in the single-walled carbon nanotube conductive slurry formula), and then the graphene dispersion, the third part of SDS (the amount of the third part of SDS accounted for 40% of the total SDS in the single-walled carbon nanotube conductive slurry formula) and the fourth part of lithium carboxymethyl cellulose + PVP (the amount of lithium carboxymethyl cellulose + PVP in the fourth part accounted for 40% of the total lithium carboxymethyl cellulose + PVP in the single-walled carbon nanotube conductive slurry formula) were added, and high-pressure dispersion was performed at a dispersion pressure of 1200 bar, and then ground at a rotation speed of 700 rpm for 4 times to obtain a mixture.

[0109] (2) Repeat step (1), add the remaining SDS (the remaining SDS accounts for 60% of the total SDS in the single-walled carbon nanotube conductive paste formula) and the remaining carboxymethyl cellulose lithium + PVP (the remaining carboxymethyl cellulose lithium + PVP accounts for 60% of the total carboxymethyl cellulose lithium + PVP in the single-walled carbon nanotube conductive paste formula), and then perform high-pressure dispersion at a dispersion pressure of 1200 bar and grinding at a rotation speed of 700 rpm to obtain a single-walled carbon nanotube conductive paste with a viscosity of 3000 cP.

[0110] Example 2

[0111] 1. Single-walled carbon nanotube conductive paste formula:

[0112] Taking the total weight of the single-walled carbon nanotube conductive slurry as 100%, the single-walled carbon nanotube conductive slurry includes KH-550 modified single-walled carbon nanotubes: 2%, graphene: 1%, total SDS: 2%, total hydroxypropyl cellulose + PVP (the mass ratio of hydroxypropyl cellulose to PVP is 1:2): 2%, and total water: 93%.

[0113] Among them, the weight ratio of KH-550 modified single-walled carbon nanotubes to graphene is 3.5:1.

[0114] The average outer diameter of the single-walled carbon nanotubes modified by KH-550 is 3.2 nm, and 3 nm ≤ X ± 2 Y ≤ 7 nm.

[0115] The graphene is made of single-layer graphene and double-layer graphene. The average value of the size of the single-layer graphene in its length direction is 1500nm, the average value of the size of the single-layer graphene in its width direction is 43nm, the average value of the size of the double-layer graphene in its length direction is 1800nm, the average value of the size of the double-layer graphene in its width direction is 44nm, and the monolayer rate is 85%.

[0116] 2. Preparation of graphene dispersion:

[0117] The graphene sheets were dispersed in the first part of water (the first part of water accounted for 40% of the total water in the single-walled carbon nanotube conductive slurry formula), and stirred at a high speed of 1100 rpm to obtain a graphene dispersion with a viscosity of 1600 mPa·s.

[0118] 3. Preparation of single-walled carbon nanotubes:

[0119] The single-walled carbon nanotubes are dispersed in KH-550 (the mass percentage of KH-550 in the solution is 4wt%), first stirred evenly, and then evenly dispersed under ultrasonic action. After the reaction is completed, the single-walled carbon nanotubes are filtered through a suction filtration mechanism. The surface of the filter membrane is the dispersed single-walled carbon nanotubes. After drying, the surface-treated single-walled carbon nanotubes are obtained.

[0120] The mass ratio of single-walled carbon nanotubes to KH-550 is 1:1.5.

[0121] 4. Preparation of Single-walled Carbon Nanotube Conductive Slurry

[0122] (1). The single-walled carbon nanotubes surface-treated with KH-550 were re-ultrasonic dispersed in the remaining water (the remaining water accounted for 60% of the total solvent amount in the single-walled carbon nanotube conductive slurry formula), and then the graphene dispersion, the third part of SDS (the amount of the third part of SDS accounted for 50% of the total SDS amount in the single-walled carbon nanotube conductive slurry formula) and the fourth part of hydroxypropyl cellulose + PVP (the amount of the fourth part of hydroxypropyl cellulose + PVP accounted for 50% of the total hydroxypropyl cellulose + PVP in the single-walled carbon nanotube conductive slurry formula) were added, and high-pressure dispersion was performed at a dispersion pressure of 1100 bar, and then ground at a rotation speed of 600 rpm for 4 times to obtain a mixture.

[0123] (2) Repeat step (1), add the remaining SDS (the remaining SDS accounts for 50% of the total SDS in the single-walled carbon nanotube conductive slurry formula) and the remaining hydroxypropyl cellulose + PVP (the remaining hydroxypropyl cellulose + PVP accounts for 50% of the total hydroxypropyl cellulose + PVP in the single-walled carbon nanotube conductive slurry formula), and then perform high-pressure dispersion at a dispersion pressure of 1100 bar and grinding at a rotation speed of 600 rpm to obtain a single-walled carbon nanotube conductive slurry with a viscosity of 3500 cP.

[0124] Example 3

[0125] 1. Single-walled carbon nanotube conductive paste formula:

[0126] Taking the total weight of the single-walled carbon nanotube conductive paste as 100%, the single-walled carbon nanotube conductive paste includes KH-550 modified single-walled carbon nanotubes: 1%, graphene: 0.6%, total CTAB: 1%, total polyvinyl alcohol + PVP (the mass ratio of polyvinyl alcohol to PVP is 1:4): 1.5%, and total water: 95.9%.

[0127] Among them, the weight ratio of KH-550 modified single-walled carbon nanotubes to graphene is 4:1.

[0128] The average outer diameter of the single-walled carbon nanotubes modified by KH-550 is 3.5 nm, and 3 nm ≤ X ± 2 Y ≤ 7 nm.

[0129] The graphene is made of single-layer graphene and double-layer graphene. The average value of the size of the single-layer graphene in its length direction is 1800nm, the average value of the size of the single-layer graphene in its width direction is 45nm, the average value of the size of the double-layer graphene in its length direction is 2000nm, the average value of the size of the double-layer graphene in its width direction is 46nm, and the monolayer rate is 90%.

[0130] 2. Preparation of graphene dispersion:

[0131] The graphene sheets were dispersed in the first part of water (the first part of water accounted for 35% of the total solvent amount in the single-walled carbon nanotube conductive slurry formula), and were stirred at a high speed of 1200 rpm to obtain a graphene dispersion with a viscosity of 1700 mPa·s.

[0132] 3. Preparation of single-walled carbon nanotubes:

[0133] The single-walled carbon nanotubes are dispersed in KH-550 (the mass percentage of KH-550 in the solution is 3wt%), first stirred evenly, and then evenly dispersed under ultrasonic action. After the reaction is completed, the single-walled carbon nanotubes are filtered through a suction filtration mechanism. The surface of the filter membrane is the dispersed single-walled carbon nanotubes. After drying, the single-walled carbon nanotubes with surface treatment are obtained.

[0134] Among them, the mass ratio of single-walled carbon nanotubes to KH-550 is 1:1.2.

[0135] 4. Preparation of Single-walled Carbon Nanotube Conductive Slurry

[0136] (1). The single-walled carbon nanotubes surface treated with KH-550 were re-ultrasonic dispersed in the remaining water (the remaining water accounted for 60% of the total water in the single-walled carbon nanotube conductive slurry formula), and then the graphene dispersion, the third part of SDS (the amount of the third part of SDS accounted for 60% of the total SDS in the single-walled carbon nanotube conductive slurry formula) and the fourth part of polyvinyl alcohol + PVP (the amount of the fourth part of polyvinyl alcohol + PVP accounted for 60% of the total polyvinyl alcohol + PVP in the single-walled carbon nanotube conductive slurry formula) were added, and high-pressure dispersion was performed at a dispersion pressure of 1000 bar, and then ground at a rotation speed of 700 rpm for 4 times to obtain a mixture.

[0137] (2) Repeat step (1), add the remaining SDS (the remaining SDS accounts for 40% of the total SDS in the single-walled carbon nanotube conductive paste formula) and the remaining polyvinyl alcohol + PVP (the remaining polyvinyl alcohol + PVP accounts for 40% of the total polyvinyl alcohol + PVP in the single-walled carbon nanotube conductive paste formula), and then perform high-pressure dispersion at a dispersion pressure of 1000 bar and grinding at a rotation speed of 700 rpm to obtain a single-walled carbon nanotube conductive paste with a viscosity of 4000 cP.

[0138] Example 4

[0139] 1. Single-walled carbon nanotube conductive paste formula:

[0140] Taking the total weight of the single-walled carbon nanotube conductive paste as 100%, the single-walled carbon nanotube conductive paste includes single-walled carbon nanotubes modified with γ-glycidyloxypropyltrimethoxysilane: 0.7%, graphene: 0.2%, total SDBS: 0.8%, total ethyl cellulose + PVP (the mass ratio of ethyl cellulose to PVP is 1:3): 0.8%, and total N-methylpyrrolidone: 97.5%.

[0141] The weight ratio of the single-walled carbon nanotubes modified with γ-glycidyloxypropyltrimethoxysilane to the graphene is 4.5:1.

[0142] The average outer diameter of the single-walled carbon nanotube modified with γ-glycidyloxypropyltrimethoxysilane is 4 nm, and 3 nm≤X±2Y≤7 nm.

[0143] The graphene is made of single-layer graphene and double-layer graphene. The average value of the size of the single-layer graphene in its length direction is 2000nm, the average value of the size of the single-layer graphene in its width direction is 48nm, the average value of the size of the double-layer graphene in its length direction is 2200nm, the average value of the size of the double-layer graphene in its width direction is 50nm, and the monolayer rate is 84%.

[0144] 2. Preparation of graphene dispersion:

[0145] The graphene sheets were dispersed in the first part of N-methylpyrrolidone (the first part of N-methylpyrrolidone accounted for 30% of the total N-methylpyrrolidone in the single-walled carbon nanotube conductive paste formula), and after high-speed stirring at 800 rpm and dispersion treatment, a graphene dispersion with a viscosity of 1800 mPa·s was obtained.

[0146] 3. Preparation of single-walled carbon nanotubes:

[0147] The single-walled carbon nanotubes are dispersed in γ-glycidyloxypropyltrimethoxysilane (the mass percentage of γ-glycidyloxypropyltrimethoxysilane in the solution is 5wt%), first stirred evenly, and then evenly dispersed under ultrasonic action. After the reaction is completed, the single-walled carbon nanotubes are filtered through a suction filtration mechanism, and the surface of the filter membrane is the dispersed single-walled carbon nanotubes. After drying, the single-walled carbon nanotubes with surface treatment are obtained.

[0148] The mass ratio of the single-walled carbon nanotube to γ-glycidyloxypropyltrimethoxysilane is 1:1.

[0149] 4. Preparation of Single-walled Carbon Nanotube Conductive Slurry

[0150] (1). The single-walled carbon nanotubes surface-treated with γ-glycidyloxypropyltrimethoxysilane were re-ultrasonic dispersed in the remaining N-methylpyrrolidone (the remaining N-methylpyrrolidone accounted for 70% of the total N-methylpyrrolidone in the single-walled carbon nanotube conductive paste formula), and then the graphene dispersion, the third part of SDBS (the third part of SDBS accounted for 40% of the total SDBS in the single-walled carbon nanotube conductive paste formula) and the fourth part of ethyl cellulose + PVP (the fourth part of ethyl cellulose + PVP accounted for 40% of the total ethyl cellulose + PVP in the single-walled carbon nanotube conductive paste formula) were added, and high-pressure dispersion was performed at a dispersion pressure of 800 bar, and then ground at a rotation speed of 700 rpm for 7 times to obtain a mixture.

[0151] (2) Repeat step (1), add the remaining SDBS (the remaining SDBS accounts for 60% of the total SDBS in the single-walled carbon nanotube conductive paste formula) and the remaining ethyl cellulose + PVP (the remaining ethyl cellulose + PVP accounts for 60% of the total ethyl cellulose + PVP in the single-walled carbon nanotube conductive paste formula), and then perform high-pressure dispersion at a dispersion pressure of 800 bar and grinding at a rotation speed of 700 rpm to obtain a single-walled carbon nanotube conductive paste with a viscosity of 4500 cP.

[0152] Example 5

[0153] 1. Single-walled carbon nanotube conductive paste formula:

[0154] Taking the total weight of the single-walled carbon nanotube conductive paste as 100%, the single-walled carbon nanotube conductive paste includes A-187 modified single-walled carbon nanotubes: 1.3%, graphene: 0.4%, total PVP: 1.4%, total hydroxypropyl cellulose + PVDC (the mass ratio of hydroxypropyl cellulose to PVDC is 1:3): 1%, and total ethanol: 95.9%.

[0155] Among them, the weight ratio of A-187 modified single-walled carbon nanotubes to graphene is 4.8:1.

[0156] The average outer diameter of the single-walled carbon nanotubes modified with A-187 is 4.5 nm, and 3 nm ≤ X ± 2 Y ≤ 7 nm.

[0157] The graphene is made of single-layer graphene and double-layer graphene. The average value of the size of the single-layer graphene in its length direction is 2200nm, the average value of the size of the single-layer graphene in its width direction is 50nm, the average value of the size of the double-layer graphene in its length direction is 2400nm, the average value of the size of the double-layer graphene in its width direction is 52nm, and the monolayer rate is 95%.

[0158] 2. Preparation of graphene dispersion:

[0159] The graphene sheets were dispersed in the first part of ethanol (the amount of the first part of ethanol accounted for 30% of the total amount of ethanol in the single-walled carbon nanotube conductive paste formula), and were stirred at a high speed of 900 rpm to obtain a graphene dispersion with a viscosity of 1900 mPa·s.

[0160] 3. Preparation of single-walled carbon nanotubes:

[0161] The single-walled carbon nanotubes are dispersed in A-187 (the mass percentage of A-187 in the solution is 5wt%), first stirred evenly, and then evenly dispersed under ultrasonic action. After the reaction is completed, the single-walled carbon nanotubes are filtered through a suction filtration mechanism. The surface of the filter membrane is the dispersed single-walled carbon nanotubes. After drying, the surface-treated single-walled carbon nanotubes are obtained.

[0162] The mass ratio of single-walled carbon nanotubes to A-187 is 1:1.

[0163] 4. Preparation of Single-walled Carbon Nanotube Conductive Slurry

[0164] (1). The single-walled carbon nanotubes surface-treated with A-187 were re-ultrasonic dispersed in the remaining ethanol (the remaining ethanol accounted for 70% of the total ethanol in the single-walled carbon nanotube conductive slurry formula), and then the graphene dispersion, the third part of PVP (the amount of the third part of PVP accounted for 40% of the total amount of PVP in the single-walled carbon nanotube conductive slurry formula) and the fourth part of hydroxypropyl cellulose + PVDC (the amount of the fourth part of hydroxypropyl cellulose + PVDC accounted for 40% of the total amount of hydroxypropyl cellulose + PVDC in the single-walled carbon nanotube conductive slurry formula) were added, and high-pressure dispersion was performed at a dispersion pressure of 1100 bar, and then ground at a rotation speed of 550 rpm for 8 times to obtain a mixture.

[0165] (2) Repeat step (1), add the remaining PVP (the remaining PVP accounts for 60% of the total PVP in the single-walled carbon nanotube conductive slurry formula) and the remaining hydroxypropyl cellulose + PVDC (the remaining hydroxypropyl cellulose + PVDC accounts for 60% of the total hydroxypropyl cellulose + PVDC in the single-walled carbon nanotube conductive slurry formula), and then perform high-pressure dispersion at a dispersion pressure of 1100 bar and grinding at a rotation speed of 550 rpm to obtain a single-walled carbon nanotube conductive slurry with a viscosity of 5000 cP.

[0166] Example 6

[0167] 1. Single-walled carbon nanotube conductive paste formula:

[0168] Taking the total weight of the single-walled carbon nanotube conductive paste as 100%, the single-walled carbon nanotube conductive paste includes KH-560 modified single-walled carbon nanotubes: 1.6%, graphene: 0.8%, total CTAB: 1.7%, total ethyl cellulose + PVDC (the mass ratio of ethyl cellulose to PVDC is 1:3): 1.7%, and total isopropyl alcohol: 94.2%.

[0169] Among them, the weight ratio of KH-560 modified single-walled carbon nanotubes to graphene is 5:1.

[0170] The average outer diameter of the single-walled carbon nanotubes modified by KH-560 is 4.8 nm, and 3 nm ≤ X ± 2 Y ≤ 7 nm.

[0171] The graphene is made of single-layer graphene and double-layer graphene. The average value of the size of the single-layer graphene in its length direction is 2400nm, the average value of the size of the single-layer graphene in its width direction is 56nm, the average value of the size of the double-layer graphene in its length direction is 2600nm, the average value of the size of the double-layer graphene in its width direction is 56nm, and the monolayer rate is 99%.

[0172] 2. Preparation of graphene dispersion:

[0173] The graphene sheets were dispersed in the first part of isopropanol (the first part of isopropanol accounted for 30% of the total isopropanol amount in the single-walled carbon nanotube conductive paste formula), and stirred at a high speed of 1200 rpm for dispersion treatment to obtain a graphene dispersion with a viscosity of 2000 mPa·s.

[0174] 3. Preparation of single-walled carbon nanotubes:

[0175] The single-walled carbon nanotubes are dispersed in a KH-560 solution (the mass percentage of KH-560 in the solution is 5wt%), first stirred evenly, and then evenly dispersed under ultrasonic action. After the reaction is completed, suction filtration is performed through a suction filtration mechanism, and the surface of the filter membrane is the dispersed single-walled carbon nanotubes. After drying, surface-treated single-walled carbon nanotubes are obtained.

[0176] The mass ratio of single-walled carbon nanotubes to KH-560 is 1:1.

[0177] 4. Preparation of Single-walled Carbon Nanotube Conductive Slurry

[0178] (1). The single-walled carbon nanotubes surface-treated with KH-560 were re-ultrasonic dispersed in the remaining isopropanol (the amount of the remaining isopropanol accounted for 70% of the total amount of isopropanol in the single-walled carbon nanotube conductive paste formula), and then the graphene dispersion, the third part of CTAB (the amount of the third part of CTAB accounted for 40% of the total amount of CTAB in the single-walled carbon nanotube conductive paste formula) and the fourth part of ethyl cellulose + PVDC (the amount of the fourth part of ethyl cellulose + PVDC accounted for 40% of the total amount of ethyl cellulose + PVDC in the single-walled carbon nanotube conductive paste formula) were added, and high-pressure dispersion was performed at a dispersion pressure of 1200 bar, and then ground at a rotation speed of 650 rpm for 9 times to obtain a mixture.

[0179] (2) Repeat step (1), add the remaining CTAB (the remaining CTAB accounts for 60% of the total CTAB in the single-walled carbon nanotube conductive paste formula) and the remaining ethyl cellulose + PVDC (the remaining ethyl cellulose + PVDC accounts for 60% of the total ethyl cellulose + PVDC in the single-walled carbon nanotube conductive paste formula), and then perform high-pressure dispersion at a dispersion pressure of 1200 bar and grinding at a rotation speed of 650 rpm to obtain a single-walled carbon nanotube conductive paste with a viscosity of 6000 cP.

[0180] Example 7

[0181] 1. Single-walled carbon nanotube conductive paste formula:

[0182] Taking the total weight of the single-walled carbon nanotube conductive paste as 100%, the single-walled carbon nanotube conductive paste includes KH-550 modified single-walled carbon nanotubes: 0.2%, graphene: 0.1%, total SDS: 0.5%, total carboxymethyl cellulose lithium + PVP (the mass ratio of carboxymethyl cellulose lithium to PVP is 1:3): 0.5%, styrene-butadiene rubber: 3%, and total water: 95.7%.

[0183] Among them, the weight ratio of KH-550 modified single-walled carbon nanotubes to graphene is 3:1.

[0184] The average outer diameter of the single-walled carbon nanotubes modified by KH-550 is 3.5 nm, and 3 nm ≤ X ± 2 Y ≤ 7 nm.

[0185] The graphene is made of single-layer graphene and double-layer graphene. The average value of the size of the single-layer graphene in its length direction is 1300nm, the average value of the size of the single-layer graphene in its width direction is 41nm, the average value of the size of the double-layer graphene in its length direction is 1500nm, the average value of the size of the double-layer graphene in its width direction is 42nm, and the monolayer rate is 80%.

[0186] 2. Preparation of graphene dispersion:

[0187] The single-layer graphene and the double-layer graphene are dispersed in the first part of water (the first part of water accounts for 30% of the total water in the single-walled carbon nanotube conductive slurry formula), and stirred at a high speed of 1000 rpm. After dispersion treatment, a graphene dispersion with a viscosity of 1500 mPa·s is obtained.

[0188] 3. Preparation of single-walled carbon nanotubes:

[0189] The single-walled carbon nanotubes are dispersed in a KH-550 solution (the mass percentage of KH-550 in the solution is 5wt%), first stirred evenly, and then evenly dispersed under ultrasonic action. After the reaction is completed, suction filtration is performed through a suction filtration mechanism, and the surface of the filter membrane is the dispersed single-walled carbon nanotubes. After drying, the surface-treated single-walled carbon nanotubes are obtained.

[0190] The mass ratio of single-walled carbon nanotubes to KH-550 is 1:1.

[0191] 4. Preparation of Single-walled Carbon Nanotube Conductive Slurry

[0192] (1). The single-walled carbon nanotubes surface-treated with KH-550 were re-ultrasonic dispersed in the remaining water (the remaining water accounted for 70% of the total water in the single-walled carbon nanotube conductive slurry formula), and then the graphene dispersion, the third part of SDS (the amount of the third part of SDS accounted for 40% of the total SDS in the single-walled carbon nanotube conductive slurry formula) and the fourth part of lithium carboxymethyl cellulose + PVP (the amount of lithium carboxymethyl cellulose + PVP in the fourth part accounted for 40% of the total lithium carboxymethyl cellulose + PVP in the single-walled carbon nanotube conductive slurry formula) were added, and high-pressure dispersion was performed at a dispersion pressure of 1200 bar, and then ground at a rotation speed of 700 rpm for 4 times to obtain a mixture.

[0193] (2) Repeat step (1), add the remaining SDS (the remaining SDS accounts for 60% of the total SDS in the single-walled carbon nanotube conductive paste formula) and the remaining carboxymethyl cellulose lithium + PVP (the remaining carboxymethyl cellulose lithium + PVP accounts for 60% of the total carboxymethyl cellulose lithium + PVP in the single-walled carbon nanotube conductive paste formula), and then perform high-pressure dispersion at a dispersion pressure of 1200 bar and grinding at a rotation speed of 700 rpm to obtain a single-walled carbon nanotube conductive paste with a viscosity of 3000 cP.

[0194] 2. Comparative Example Single-walled carbon nanotube conductive slurry and preparation method thereof:

[0195] Comparative Example 1

[0196] Compared with Example 1, no graphene is added.

[0197] Comparative Example 2

[0198] Compared with Example 1, the single-walled carbon nanotubes are not surface treated.

[0199] Comparative Example 3

[0200] Compared with Example 1, Step 1 and Step 3 are the same. After Step 2 of Example 1 is performed, the preparation steps of the single-walled carbon nanotube conductive paste are as follows:

[0201] Surface-treated single-walled carbon nanotubes and remaining water (the remaining water accounts for 70% of the total water in the single-walled carbon nanotube conductive slurry formula) are added to the graphene dispersion, and the mixture is stirred at a high speed of 1200 rpm and dispersed for 10 minutes. SDS (SDS accounts for 40% of the total SDS in the single-walled carbon nanotube conductive slurry formula) and lithium carboxymethyl cellulose + PVP (lithium carboxymethyl cellulose + PVP accounts for 40% of the total lithium carboxymethyl cellulose + PVP in the single-walled carbon nanotube conductive slurry formula) are added, and the mixture is stirred at a high speed of 1200 rpm and dispersed for 80 minutes to 120 minutes to obtain a single-walled carbon nanotube conductive slurry.

[0202] Comparative Example 4

[0203] Compared with Example 1, no single-walled carbon nanotubes were added, and only multi-walled carbon nanotubes (with a diameter ranging from 15 nm to 40 nm) were added.

[0204] A lithium-ion battery using the single-walled carbon nanotube conductive paste of an embodiment of the present application is provided below:

[0205] 1. Pole preparation:

[0206] According to the mass ratio of silicon dioxide (SiO), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and single-walled carbon nanotube conductive slurry solid matter (single-walled carbon nanotube + graphene) of 97.4:1.6:0.5:0.5, silicon dioxide and CMC are added to the aqueous carbon nanotube conductive slurry to prepare the negative electrode ingredients, and then deionized water is added to adjust the solid content to 35wt%, and then put into a double planetary mixer for vacuum high-speed homogenization, the revolution speed is adjusted to 2000RPM, the rotation speed is adjusted to 800RPM, and after homogenization for 20min, it is coated on the negative electrode collector and dried at 80°C to obtain the negative electrode sheet, and then the sheet resistance of the negative electrode sheet is tested under a pressure of 40KG. The test results are shown in Table 1.

[0207] 2.Battery assembly and testing

[0208] The negative electrode sheet was cut to serve as the negative electrode, and the positive electrode was made of lithium cobalt oxide to prepare a CR2032 button battery, which was tested on a Blue Electric test system.

[0209] The charge and discharge conditions were set as follows: charge to a cut-off voltage of 1.5 V, discharge to a cut-off voltage of 0.005 V, cycle at 0.1 C for 5 weeks, and cycle at 1 C for 100 weeks, to obtain the 0.1 C charge capacity, 1 C charge capacity, and 1 C cycle retention rate for 100 weeks of the CR2032 button battery. The test results are shown in Table 1.

[0210] Table 1

[0211]

[0212] As can be seen from Table 1, compared with Comparative Example 1, Example 1 of the present application does not add graphene, which leads to the easy agglomeration of the bundles of single-walled carbon nanotubes, poor dispersion of single-walled carbon nanotubes, and significant decrease in the overall conductivity of the single-walled carbon nanotube conductive slurry. As a result, the sheet resistance of the negative electrode sheet is high, the battery's 0.1C charging capacity, 1C charging and 1C cycle 100-week retention rate capacity are all low, the battery has a short service life and poor effect.

[0213] Compared with Example 2, the single-walled carbon nanotubes in Example 2 are not surface treated, which results in the bundles of single-walled carbon nanotubes being easily agglomerated, and the dispersion performance of the single-walled carbon nanotubes being poor, which significantly reduces the overall conductivity of the single-walled carbon nanotube conductive paste. As a result, the sheet resistance of the negative electrode sheet is high, the battery's 0.1C charging capacity, 1C charging, and 1C cycle 100-week retention rate capacity are all low, and the battery has a short service life and poor effect.

[0214] Compared with Comparative Example 3, the preparation method in Comparative Example 3 is changed in Example 1 of the present application, which affects the uniformity of the dispersion of the single-walled carbon nanotubes, thereby affecting the formation of the conductive network, and significantly reducing the overall conductivity of the single-walled carbon nanotube conductive slurry. As a result, the sheet resistance of the negative electrode sheet is high, the battery's 0.1C charging capacity, 1C charging and 1C cycle 100-week retention rate capacity are all low, the battery has a short service life and poor effect.

[0215] Compared with Example 4, the carbon nanotubes in Example 4 are not single-walled carbon nanotubes, and the conductivity is reduced. As a result, the sheet resistance of the negative electrode sheet is high, the battery's 0.1C charging capacity, 1C charging and 1C cycle 100 cycle retention capacity are all low, the battery has a short service life and poor effect.

[0216] Compared with Example 1, Examples 2-6 of the present application are only slightly different in the formula of the single-walled carbon nanotube conductive paste and some parameters in the process. Therefore, compared with Comparative Examples 1-4, Examples 2-6 can make the bundles of single-walled carbon nanotubes less likely to agglomerate, and the dispersion performance of single-walled carbon nanotubes is better, so that the overall conductivity of the single-walled carbon nanotube conductive paste is significantly improved. Therefore, the sheet resistance of the negative electrode sheet is low, the battery's 0.1C charging capacity, 1C charging and 1C cycle 100-week retention rate capacity are all high, and the battery has a long service life and good effect.

[0217] Compared with Example 1, Example 7 of the present application only adds styrene-butadiene rubber as a binder. Therefore, compared with Comparative Examples 1-4, Example 7 can make the bundles of single-walled carbon nanotubes less likely to agglomerate as much as possible, and the dispersion performance of single-walled carbon nanotubes is better, so that the overall conductivity of the single-walled carbon nanotube conductive paste is significantly improved. Therefore, the sheet resistance of the negative electrode plate is low, the battery's 0.1C charging capacity, 1C charging and 1C cycle 100-week retention rate capacity are all high, and the battery has a long service life and good effect.

[0218] Only the contents related to the invention are introduced here. The rest can be obtained by referring to the relevant technology and will not be described in detail here.

[0219] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A single-walled carbon nanotube conductive paste, characterized in that: Taking the total weight of the single-walled carbon nanotube conductive paste as 100%, the single-walled carbon nanotube conductive paste comprises: Modified single-walled carbon nanotubes, 0.2%-2%; wherein the modified single-walled carbon nanotubes include single-walled carbon nanotubes modified by coupling agents; Graphene, 0.1%-1%; wherein the graphene comprises at least a single layer of graphene; Total surfactant, 0.5%-2%; Total dispersant, 0.5%-2%; Total solvents, 93%-98.7%.

2. The single-walled carbon nanotube conductive paste according to claim 1, characterized in that: The single-walled carbon nanotube conductive paste further comprises, by weight: Binder, 0.5%-3%.

3. The single-walled carbon nanotube conductive paste according to claim 1 or 2, characterized in that: The weight ratio of the modified single-walled carbon nanotube to the graphene is in the range of 3:1-5:

1.

4. The single-walled carbon nanotube conductive paste according to claim 1 or 2, characterized in that: The average outer diameter of the modified single-walled carbon nanotubes is less than 5 nm; The average outer diameter of the modified single-walled carbon nanotubes is set to X, the standard deviation of the outer diameter of the modified single-walled carbon nanotubes is set to Y, 3nm≤X±2Y≤7nm; wherein 0<Y≤1.

5. The single-walled carbon nanotube conductive paste according to claim 1 or 2, characterized in that: The graphene is a single-layer graphene, and a size of the single-layer graphene in a length direction is greater than 1000 nm, and a size in a width direction is less than or equal to 100 nm.

6. The single-walled carbon nanotube conductive paste according to claim 1 or 2, characterized in that: The graphene is composed of a single-layer graphene and a double-layer graphene, wherein the size of the single-layer graphene in the length direction is greater than 1000 nm and the size in the width direction is less than or equal to 100 nm, and the size of the double-layer graphene in the length direction is greater than 1000 nm and the size in the width direction is less than or equal to 100 nm; and / or, The percentage content of the single-layer graphene in the graphene is greater than or equal to 80%.

7. A lithium ion battery, characterized in that: It comprises a negative electrode plate, wherein the negative electrode plate comprises the single-walled carbon nanotube conductive paste according to any one of claims 1 to 6.

8. A method for preparing a single-walled carbon nanotube conductive paste according to any one of claims 1 to 6, characterized in that: The steps include: Step 1, forming a graphene dispersion and the modified single-walled carbon nanotubes respectively; Step 2: dispersing the modified single-walled carbon nanotubes into the second part of the solvent, adding the graphene dispersion, the third part of the surfactant and the fourth part of the dispersant, performing a dispersion treatment at a first pressure, and then performing a grinding treatment at a first speed to obtain a mixture; wherein the second part of the solvent is a part of the total solvent; Step three, adding the fifth part of the surfactant and the sixth part of the dispersant to the mixture, and then repeating the steps of dispersing under the first pressure and grinding at the first speed in step two to obtain the single-walled carbon nanotube conductive slurry; wherein the fifth part of the surfactant is the remaining surfactant in the total surfactant except the third part of the surfactant, and the sixth part of the dispersant is the remaining dispersant in the total dispersant except the fourth part of the dispersant.

9. The method for preparing the single-walled carbon nanotube conductive paste according to claim 8, characterized in that: Forming the modified single-walled carbon nanotubes comprises: The single-walled carbon nanotubes are dispersed in a coupling agent solution for dispersion treatment, and then filtered and dried to obtain the modified single-walled carbon nanotubes.

10. The method for preparing the single-walled carbon nanotube conductive paste according to claim 8, characterized in that: Forming the graphene dispersion comprises: The graphene is dispersed in the first part of the solvent for dispersion treatment to obtain the graphene dispersion liquid; wherein the first part of the solvent is the solvent in the total solvent except the second part of the solvent.

Citation Information

Cited By

  • Graphene nanobelt slurry as well as preparation method and application thereof

    CN122059401A